Constituição e Realização do Crédito Tributário na Justiça do Trabalho - Silva, Jean Paolo Simei e (2016)
This thesis focus on the generation of pension credits arising from ratified settlements and convictions in Labor Courts, by questioning the influence thereof on the loss of a procedural right and lapse, as well as on the initial term of default interest. Logical-semantic constructivism is the method chosen to approach the subject matter analyzed herein, making use of constitutional wording changed by Amendments No. 20/1998 and 45/2004, in addition to infra-legal changes institutionalizing a new legal paradigm, along with Higher Court decisions. This study shows the progress of concepts through consecutive legislative doctrinal changes resulting from orders. Doctrinal and jurisprudential trend states that although these changes are constitutional, they created an anomalous or sui generis entry, and such peculiarity has given rise to loss of procedural right or lapse times that are noncompliant with constitutional taxation system, so that the parameters of social security contributions would vary according to the organ they come from. Through legal literature and jurisprudential research, especially in courts aiming at the steadiness of the trials, we have the appropriate index to establish a prognosis showing that changes in empirical and normative parameters no longer support known classification models, and we present herein the classification criteria encompassing this new element that seems not to suit current doctrine, i.e. legal tax credit. Such credit is very similar to that given by public administration, and lapse figures as a distinctive point. Therefore, we will discuss the definition of the concept of tax credit in order to assess, from such point, its generation under the scope of Labor Court, also covering the topics of loss of a procedural right and lapse. Prescriptive description of tax credit in CTN [Brazilian Taxation Code] served as conceptual basis to give rise to 1988 Constitution, and an extensive doctrine has been developed based on it; however, it does not support useful legal classification